Privatization of the Japan Highway Public Corporation: Policy Assessment - Fumitoshi Mizutani; Shuji Uranishi (European Regional Science Association (ERSA), 2006)
Unlike the expressway systems of the U.S. and Europe, where road use is largely free of charge, the Japanese expressway system consists mostly of toll roads. The toll expressway system was instituted after World War II to expedite construction of a nation-wide expressway network. Originally it was intended that the system ultimately become free of charge, as soon as the national expressway network was completed and construction debts repaid. Although expressway tolls are collected based on each individual route, tolls are included in the same budget and pooled for the construction of other routes, in what is called a pool system. However, problems have occurred in such a system. Expressway users have been required to continue paying expressway tolls along trunk expressways near big cities where construction costs have long been completely repaid. Furthermore, in rural areas where the demand for expressway use is low, the system continues to construct expressways simply because rural residents expect them to be constructed. Users have also been dissatisfied with the high price of expressway use, attributing the cost to what they have perceived as the monopolistic nature of the public corporation system, which, like the former Japan National Railway, had no competition. In this environment, Prime Minister Koizumi appointed a special committee to define the role of the Japan Highway Public Corporation and to determine whether or not it should be privatized, and the issue of highway privatization became controversial in Japan. Although there were effective arguments pro and con, it was decided that the corporation be privatized. In October, 2005, the Japan Highway Public Corporation was privatized and separated into three expressway companies, and the following companies were also privatized: the Metropolitan Expressway Public Corporation, the Hanshin Expressway Public Corporation, and the Honshu-Shikoku Bridge authority. The main purpose of this study is to assess the privatization policy taken by the government. The aspects which we will especially focus on are (1) ownership, (2) regional subdivision, (3) cost structure, (4) investment behavior, (5) pricing system, (6) management and incentive system of internal organization, (7) public regulations, and (8) political intervention. We will evaluate these aspects comparing the before-privatization and after-privatization periods of the Japan Expressway Public Corporation. As the performance results of the new organization are not available yet because privatization is quite recent, our conceptual outcomes will be based on theory and the lessons learned from the privatization of the Japan National Railway.
Keywords: 330